Heritable Changes in Physiological Gas Exchange Traits in Response to Long-Term, Moderate Free-Air Carbon Dioxide Enrichment - Holohan, Aidan David; Müller, Christoph; McElwain, Jennifer (Frontiers in Plant Science, 2019)
Atmospheric carbon dioxide ([CO2]) concentrations significantly alter developmental plant traits with potentially far-reaching consequences for ecosystem function and productivity. However, contemporary evolutionary responses among extant plant species that coincide with modern, anthropogenically driven [CO2] rise have rarely been demonstrated among field-grown plant populations. Here we present findings from a long-term, free-air carbon dioxide enrichment (FACE) study in a seminatural European grassland ecosystem in which we observe a differential capacity among plant species to acclimate intrinsic water-use efficiencies (WUEs) in response to prolonged multigenerational exposure to elevated [CO2] concentrations. In a reciprocal swap trial, using controlled environment growth chambers, we germinated seeds from six of the most dominant plant species at the FACE site [Arrhenatherum elatius (L.), Trisetum flavescens (L.), Holcus lanatus (L.), Geranium pratense (L.), Sanguisorba officinalis (L.), and Plantago lanceolata (L.)]. We found that long-term exposure to elevated [CO2] strongly influenced the dynamic control of WUEi in the first filial generations (F1) of all species as well as an unequal ability to adapt to changes in the [CO2] of the growth environment among those species. Furthermore, despite trait–environment relationships of this nature often being considered evidence for local adaptation in plants, we demonstrate that the ability to increase WUEi does not necessarily translate to an ecological advantage in diverse species mixtures.